The impacts of forest degradation on medicinal plant use and implications for health care in Eastern Amazonia - Shanley, P.; Luz, L. (2003)
Over the last three decades, forest degradation in the Brazilian Amazon has diminished the availability of some widely used medicinal plant species. Results of a 9-year market study suggest that forests represent an important habitat for medicinal plants used in eastern Amazonia: Nine of the twelve top-selling medicinal plants are native species, and eight are forest based. Five of the top-selling species have begun to be harvested for timber, decreasing the availability of their barks and oils for medicinal purposes. Many of these medicinal plants have no botanical substitute, and pharmaceuticals do not yet exist for some of the diseases for which they are used. Market surveys indicate that all socioeconomic classes in Amazonia use medicinal plants because of cultural preferences, low cost, and efficacy. Degradation of Amazonian forests may signify not only the loss of potential pharmaceutical drugs for the developed world but also the erosion of the sole health care option for many of Brazil’s rural and urban poor.